Kelayakan Booklet Inventarisasi Tumbuhan Berkhasiat Obat sebagai Media Pembelajaran - Ruqiah Ganda Putri Panjaitan*; Titin Titin; Eko Sri Wahyuni (Jurnal Pendidikan Sains Indonesia, 2021)
Learning media is a tool in delivering learning material. The use of instructional media is proven effective in increasing understanding of a material. It's just that, the learning media used today tend to only contain material taken from textbooks, even though the media can also be developed based on the results of research or observations made in the field or in the laboratory. This study aims to determine the feasibility of the booklet developed by the inventory of medicinal plants in Pontianak City as a learning medium. The research stages include determining potentials and problems, gathering information, designing booklets, validating booklets, and revising booklets. The initial stage of making a booklet is to carry out an inventory of medicinal plant species and design the contents. The feasibility of the booklet is seen from the evaluation by the validator. The research instrument was a validation sheet. The aspects assessed include aspects of format, content, and language. From the six indicators on the format aspect, validity 1 is obtained, from two three indicators in the content aspect, validity is obtained 1, and from the two indicators on the language aspect, validity is obtained. 1. Overall, from the three aspects, the average validity is 1 with very high criteria. It can be concluded that this booklet is suitable for use as a learning medium